Singing the New Song : Literacy and Liturgy in Late Medieval England - Zieman, Katherine (Book collections on Project MUSE., 2008)
In Singing the New Song, Katherine Zieman examines the institutions and practices of the liturgy as central to changes in late medieval English understandings of the written word.